Effects of Acute Exposure to 3500 MHz (5G) Radiofrequency Electromagnetic Radiation on Anxiety‐Like Behavior and the Auditory Cortex in Guinea Pigs. Issue 2 (23rd January 2022) - Yang, Honghong; Zhang, Yuanyuan; Wu, Xianwen; Gan, Ping; Luo, Xiaoli; Zhong, Shixun; Zuo, Wenqi
Abstract : Numerous studies have shown that radiofrequency electromagnetic radiation (RF‐EMR) may negatively affect human health. We detected the effect of 3500 MHz RF‐EMR on anxiety‐like behavior and the auditory cortex (ACx) in guinea pigs. Forty male guinea pigs were randomly divided into four groups and exposed to a continuous wave of 3500 MHz RF‐EMF at an average specific absorption rate (SAR) of 0, 2, 4, or 10 W/kg for 72 h. After exposure, malondialdehyde (MDA) levels, antioxidant enzyme activity, anxiety‐like behavior, hearing thresholds, cell ultrastructure, and apoptosis were detected. Our results revealed that hearing thresholds and basic indexes of animal behavior did not change significantly after exposure ( P  > 0.05). However, the MDA levels of ACx were increased ( P  < 0.05), and catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GSH‐px) activities were decreased ( P  < 0.05) in the exposure groups compared to the sham group. Ultrastructural changes of ACx, including swollen mitochondria and layered myelin sheaths, were observed. Cytochrome‐c relocalization, caspase‐9, and cleaved caspase‐3 activation were detected in the exposure groups. In conclusion, these results suggest that oxidative stress is an important mechanism underlying the biological effects of RF‐EMR, which can induce ultrastructural damage to the ACx and cell apoptosis through a mitochondria‐dependent mechanism. Moreover, oxidative stress, apoptosis induction and ultrastructural damage increase in a SAR‐dependent manner. However, RF‐EMR does not increase hearing thresholds or induce anxiety. Bioelectromagnetics. 43:106–118, 2022. © 2021 Bioelectromagnetics Society.